The Localization of Pharmaceutical Clinical Research in Europe - Greta Falavigna; Roberto Ippoliti (Baqiyatallah University of Medical Sciences, 2017)
Background: Clinical research is a specific phase of the production process in the pharmaceutical industry in which companies test candidate drugs on patients in order to collect clinical evidence about safety and effectiveness. Objective: This paper is an operational research which aimed to support the hypothesis that pharmaceutical clinical research is like any other production process which could be localized where the cost is most competitive. In other words, this work aimed to demonstrate that the localization process of this specific phase of the pharmaceutical industry's R&D is based on the price of clinical evidence. Methods: Considering Europe and taking panel data into account, an efficiency frontier through data envelopment analysis (DEA) was estimated. The efficiency of countries in maximizing the number of innovative medical treatments, given their available resources was estimated. Afterwards, focusing on European macro-regions, authors analyzed whether a significant concentration of clinical research exists. Results: Results suggest that, taking the expected principal investigators' fee into account, Southeastern Europe and Central Eastern Europe are the most attractive macro-regions for the pharmaceutical industry's foreign direct investments in clinical research. Conclusion: The results of the proposed operational research cannot reject the suggested evolution of the pharmaceutical industry's clinical research. In other words, results confirm the localization process of the testing phase in East Europe, where the expected principal investigators' fee is more competitive.